Controlling the Origins of Inflammation with a Photoactive Lipopeptide Immunopotentiator1. Issue 20 (20th March 2015) - Mancini, Rock J.; Stutts, Lalisa; Moore, Troy; Esser‐Kahn, Aaron P.
Abstract Inflammatory immune responses are mediated by signaling molecules that are both produced by and recognized across highly heterogeneous cell populations. As such, the study of inflammation using traditional immunostimulants is complicated by paracrine and autocrine signaling, which obscures the origin of a propagating response. To address this challenge, we developed a small‐molecule probe that can photosensitize immune cells, thus allowing light‐mediated inflammation. This probe was used to control the origin of inflammation using light. Following this motif, inflammation was initiated from fibroblasts or dendritic cells. The contributions of fibroblasts and dendritic cells in initiating inflammation in heterogeneous co‐culture are reported, thus providing insights into the future development of vaccines and treatment of inflammation.